Empirical Study on the Temporal Metaphors 前qián and 后hòu in Chinese, Korean, Spanish and German - Xin, Wei; Jingyi, Yan; Yazhi, Cai (Sinología hispánica. China Studies Review, 2025)
As a universal phenomenon, space-time metaphors are found in numerous languages and cultures around the world. Despite linguistic differences among speakers of different languages, these metaphors provide a fascinating means to explore how people conceive and verbalize time and space. In our study, we conducted three experiments with speakers of Chinese, Spanish, German, and Korean, focusing on their metaphorical preferences and the reasons behind their linguistic choices. In experiments I and II, we used visual stimuli to assess metaphorical preferences. We observed that speakers of Chinese and Korean tend to prefer the metaphor "TIME IS MOVEMENT," while speakers of Spanish and German opt for "EGO IS MOVEMENT." This suggests differences in how these groups conceptualize time and its movement. Experiment III consisted of a series of questions designed to delve deeper into how these speakers perceive time. The results indicated that the Chinese and Korean groups pay more attention to the past, while Spanish and German speakers focus more on the future. These differences reflect significant cultural and linguistic variations in time perception and can influence intercultural communication.